PERANAN PENGURUS KELOMPOK TANI DALAM PROGRAM PENGEMBANGAN USAHA PANGAN MASYARAKAT DI KECAMATAN PALAS KABUPATEN LAMPUNG SELATAN PROVINSI LAMPUNG - Maghfira Hariani; Sumaryo G S; Begem Viantimala (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This research aims to know the role level of farmer group administrators, and he factors related to the roles of farmer group administrators in community food developmant program (PUPM). Data of this research were collected from January to February 2019. This research uses a survey method and data are analyzed by descriptive and Rank Spearman analysis. The sample of the research is 2 Gapoktan from 2 villages which is taken puposively i.e Gapoktan Sejahtera (19 farmer groups) and Gapoktan Bersama (26 farmer groups). Then, from each farmer group is chosen 5 administrators consisting of leader, secretary, treasurer and 2 administrator members. Therefore, the number of samples is 69 administrators of farmer groups joining the program. The results of this research showed that the role lavel of farmer group administrators in the PUPM Program in Palas Subdistrict, South Lampung Regency is in the high classification. Factors related to the roles of farmer group administrators in the PUPM program are the education level and the motivation level of farmer group administrators.Key words: administrator, farmer groups, PUPM